Biofabrication of copper oxide nanoparticles using Dalbergia sisso leaf extract for antibacterial, antibiofilm and antioxidant activities - Muhammad Hussnain Siddique; Maimona Sadia; Saima Muzammil; Muhammad Saqalein; Asma Ashraf; Sumreen Hayat; Saba Saba; Arif Muhammad Khan; Abeer Hashem; Graciela Dolores Avila-Qezada; Elsayed Fathi Abd-Allah (Scientific Reports)
Abstract One of the biggest challenges encountered by the current generation is the evolution of antibiotic resistant bacteria as a result of excessive and inappropriate use of antibiotics. This problem has led to the development of alternative approaches to treat the diseases caused by these multidrug resistant bacteria (MDR). One of the most promising and novel approaches to combat these pathogens is utilization of nanomaterials as antimicrobial agents. In the current investigation, copper oxide nanoparticles (CuO NPs) were fabricated by green method using Dalbergia sissoo leaf extract. The fabricated nanoparticles were characterized through various techniques like UV–visible spectroscopy, scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). The UV–visible spectroscopy revealed an absorption peak at 290 nm. SEM micrograph revealed only few spherical nanoparticles (with average diameter of < 100 nm), whereas most of the CuO NPs were agglomerated and formed large clusters. FTIR indicated presence of different functional groups that were used as reducing and capping agents while XRD analysis showed crystalline phase structure for the nanoparticles. These nanoparticles exhibited significant growth inhibition in terms of maximum inhibitory zones of 24 mm with minimum inhibitory concentrations (MIC) ranging from 62.5 to 125 µg/ml against MDR bacteria such as Acinetobacter baumannii, Staphylococcus aureus, Escherichia coli and Klebsiella pneumoniae. The effect of different concentrations of nanoparticles on cell membrane disruption was also investigated and a significant increase (p < 0.05) in the leakage of cellular content such as DNA, proteins and reducing sugar was measured. These nanoparticles also showed antibiofilm potential and a significant increase (p < 0.05) in biofilm inhibition was observed by increasing the concentration of nanoparticles. It was noted that percentage of inhibition of biofilm was found to be 68.4–75.8% at the highest tested concentration. The combined effects of antibiotics and nanoparticles revealed a synergistic interaction between them against tested bacteria. In vitro antioxidant activity of fabricated nanoparticles revealed significant antioxidant potential (p < 0.05) by quenching free radicals such as DPPH (73.6%), ABTS (68%) and H2O2 (63%) in a dose-dependent manner.